The Pattern of Copper Release in Copper‐Based Nanoparticles Regulates Tumor Proliferation and Invasiveness in 3D Culture Models - Jose I. Garcia‐Peiro; Paula Guerrero‐López; Felipe Hornos; Jose L. Hueso; J. Manuel Garcia‐Aznar; Jesus Santamaria (Small Science)
Cancer is a leading cause of death worldwide. Glioblastoma (GBM) is a major challenge in oncology due to its highly invasive nature and limited treatment options. GBM's aggressive migration beyond tumor margins and rapid tumor growth hinders success in patient treatment. Localized therapeutic delivery, such as the use of transition metals like copper, is highlighted as a novel therapeutic agent for many potential biomedical applications. Herein, it is aimed to study the effects of Cu release on the proliferation and invasiveness of cancer cells. To this end, novel copper‐based nanostructures with different release patterns are designed. Using a complex 3D cell culture model to mimic the tumor microenvironment, it is shown that different patterns of copper ion release have a strong impact on GBM progression and invasiveness. The findings highlight the importance of optimizing localized copper release patterns to tailor different tumor treatment strategies. They also show the potential and suitability of 3D microchips as instruments to study the behavior of tumor spheroids. In spite of their limitations, these 3D microdevices enable a controlled and close monitoring of the influence of environmental factors (such as the presence of Cu ions) on the proliferation and invasiveness of the cells, with a better approach to reality compared to 2D models and with a more controlled environment, compared to an in vivo model.